A gap function and existence of solutions for a non-smooth vector variational inequality on Hadamard manifolds. (2nd September 2021) - Jayswal, Anurag; Kumari, Babli; Ahmad, Izhar
Abstract : In the present paper, a gap function for a non-smooth mixed weak vector variational inequality involving generalized gradient on Hadamard manifolds is obtained. A non-trivial example is presented to illustrate the relationship between a gap function and a non-smooth mixed weak vector variational inequality. The existence of solution for a non-smooth mixed weak vector variational inequality without monotonicity is also studied. Moreover, a g -pseudomonotone is introduced and it is employed to discuss the existence of solution for an aforesaid problem.